The longest war Northern Ireland's troubled history - Mulholland, Marc 1971- (University press, 2002)
"The Troubles" in Northern Ireland have proved one of the most intractable conflicts in Europe since World War II, consistently attracting international attention, particularly from the United States. This exploration of the central issues and debates about Northern Ireland sets them in the historical context of hundreds of years of conflict.